SOX2 Is the Determining Oncogenic Switch in Promoting Lung Squamous Cell Carcinoma from Different Cells of Origin - Ferone, Giustina; Song, Ji-Ying; Sutherland, Kate D; Bhaskaran, Rajith; Monkhorst, Kim; Lambooij, Jan-Paul; Proost, Natalie; Gargiulo, Gaetano; Berns, Anton (Cancer cell, 2016)
Lung squamous cell carcinoma (LSCC) is a devastating malignancy with no effective treatments, due to its complex genomic profile. Therefore, preclinical models mimicking its salient features are urgently needed. Here we describe mouse models bearing various combinations of genetic lesions predominantly found in human LSCC. We show that SOX2 but not FGFR1 overexpression in tracheobronchial basal cells combined with Cdkn2ab and Pten loss results in LSCC closely resembling the human counterpart. Interestingly, Sox2;Pten;Cdkn2ab mice develop LSCC with a more peripheral location when Club or Alveolar type 2 (AT2) cells are targeted. Our model highlights the essential role of SOX2 in commanding the squamous cell fate from different cells of origin and represents an invaluable tool for developing better intervention strategies.